2021
DOI: 10.1007/s10888-021-09499-2
|View full text |Cite|
|
Sign up to set email alerts
|

The fall in income inequality during COVID-19 in four European countries

Abstract: We here use panel data from the COME-HERE survey to track income inequality during COVID-19 in France, Germany, Italy, and Spain. Relative inequality in equivalent household disposable income among individuals changed in a hump-shaped way between January 2020 and January 2021, with an initial rise from January to May 2020 being more than reversed by September 2020. Absolute inequality also fell over this period. Due to the pandemic some households lost more than others, and government compensation schemes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 25 publications
5
50
0
1
Order By: Relevance
“…As Clark et al (2020) have recently underlined, we observe a fast-growing literature on the impact of lockdowns on well-being (e.g. Layard et al, 2020;Brodeur et al, 2021), labor market participation (e.g.…”
Section: Literature Review and Empirical Approachmentioning
confidence: 81%
“…As Clark et al (2020) have recently underlined, we observe a fast-growing literature on the impact of lockdowns on well-being (e.g. Layard et al, 2020;Brodeur et al, 2021), labor market participation (e.g.…”
Section: Literature Review and Empirical Approachmentioning
confidence: 81%
“…In this regard, [10], argues that, at least during the first year of the pandemic, global inequality declined because of COVID-19, since per capita income decreased more in higher income countries. Similarly, [11] state that in the case of France, Germany, Spain, Italy, and Sweden, inequality in income distribution grew in the first months of the pandemic and, from September 2020, it began to reduce as a result of public policies that would have benefited the poorest more, as is also the case in the United Kingdom, where consumer spending fell less during the pandemic in lower income households, as their income decreased less as a result of the increase in public benefits [12]. In fact, according to [13], without compensatory public policies, wage inequality, and poverty would increase in the United States for all social groups and states.…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…A year later, the newest research works on this topic confirm that Member States' interventions were mostly successful in reducing absolute inequalities to pre-pandemic times. This effect (following an initial increase in income inequality in the early months of 2020) was measured over the first three quarters of 2020 in France, Germany, Italy, and Spain (Clark et al, 2021) but not in Sweden (Angelov & Waldenström, 2021). Eurostat (2021) confirmed that "poverty remains stable at EU level, with a high heterogeneity across countries and different segments of the population."…”
Section: Food Consumption Income and Covid-19mentioning
confidence: 96%
“…A year later, the newest research works on this topic confirm that Member States' interventions were mostly successful in reducing absolute inequalities to pre‐pandemic times. This effect (following an initial increase in income inequality in the early months of 2020) was measured over the first three quarters of 2020 in France, Germany, Italy, and Spain (Clark et al, 2021) but not in Sweden (Angelov & Waldenström, 2021). Eurostat (2021) confirmed that “poverty remains stable at EU level, with a high heterogeneity across countries and different segments of the population.” According to Stantcheva (2021), who found that, in the G7 countries, household incomes increased during the pandemic while GDP fell sharply, “without governmental support, the pandemic would have increased income inequalities, hitting harder the bottom of the income distribution.”…”
Section: Food Consumption Income and Covid‐19mentioning
confidence: 97%